AUTOMATION WORK ORDER AND MASTER PRODUCTION SCHEDULE IN ENTERPRISE RESOURCES PLANNING FOR PT SFP - Reka, Nadia Revina (IT for Society, 2024)
In today's dynamic business landscape, manufacturing enterprises like PT SFP face the constant challenge of optimizing their production processes to remain competitive. The Enterprise Resources Planning (ERP) architecture will be used to develop an integrated solution to automate work order administration and master production scheduling. The production and planning division is a very important process and is interconnected with one another. Since manufacturing is the most demanding business process in a company's activities, the significance of the planning system is greatly raised. Even though the company already has an ERP system that is quite integrated, there are still many processes that are still carried out offline which causes manual inefficiency, this not only increases waiting time but can also cause anomalies. This project provides ERP development ideas, especially in the Production and Planning module for PT SFP by implementing automation and integration in the work order planning workflow to improve business processes. It includes the business process of creating Order Confirmation (OC) Receiving Date Input, and automation of planning work order creation, usage standards in the work order and the work order itself. This system is expected to be more effective and efficient in the field of production planning using ERP web-based that can be accessed online.